Report on the 6th ADBIS’2002 conference - Bieliková, Mária; Návrat, Pavol; Manolopoulos, Yannis (Computing and Informatics, 2012)
The 6th East European Conference ADBIS 2002 was held on September 8–11, 2002 in Bratislava, Slovakia. It was organised by the Slovak University of Technology (and, in particular, its Faculty of Electrical Engineering and Information Technology) in Bratislava in co-operation with the ACM SIGMOD, the Moscow ACM SIGMOD Chapter, and Slovak Society for Computer Science. The call for papers attracted 115 submissions from 35 countries. The international program committee, consisting of 43 researchers from 21 countries, selected 25 full papers and 4 short papers for a monograph volume published by the Springer Verlag. Beside those 29 regular papers, the volume includes also 3 invited papers presented at the Conference as invited lectures. Additionally, 20 papers have been selected for the Research communications volume. The authors of accepted papers come from 22 countries of 4 continents, indicating the truly international recognition of the ADBIS conference series. The conference had 104 registered participants from 22 countries and included invited lectures, tutorials, and regular sessions. This report describes the goals of the conference and summarizes the issues discussed during the sessions.